Comparative analysis of fitness coach training systems - Ilya Krugovykh; Vitaliy Avsiyevich; Zhanna Sabyrbek; Toktassyn Bekbolatov; Sharkul Taubayeva (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The purpose of this study was to identify and study the most effective practices used in coach training systems in various countries of the world. The following methods of scientific cognition were used: comparative analysis, systematic method, and classification. As a result of the conducted research, an in-depth analysis of fitness coach training systems in the United States of America, Norway, Spain, and Kazakhstan was carried out. It was determined that in the American fitness coach training system, a distinctive feature is a high diversity of educational programmes, which is supported by the standardisation of qualifications. In the context of the Norwegian training system, an emphasis was placed on maintaining and developing the principles of health and activity, and on the professional ethics of specialists, including psychological training and interaction with clients. Consideration of the Spanish approach demonstrated the importance of aesthetics and diversity of physical activity for local educational programmes. The specific features of training fitness coaches in Spain also include issues of motivation and psychological training of future specialists. In Kazakhstan, a combination of conventional and innovative methods in the training of fitness coaches has been revealed, which consists in studying the pedagogical approach and introducing the latest trends in fitness. A detailed examination of the above systems helped to identify key differences in approaches to ethics and responsibility of coaches. Based on the analysis, a universal approach to training fitness coaches based on best practices was developed and described.